Pengaruh Model Pembelajaran Snowball Throwing Terhadap Hasil Belajar Mahasiswa Program Studi Pendidikan Biologi Universitas Khairun - Vianti, Eva; Tuara, Zulkifli I.; Tamalene, M. Nasir; Apling, Mujais; Ihsan, Ikhlashul; Juma, Yusri (Jurnal Ilmiah Wahana Pendidikan, 2025)
The purpose of this study is to ascertain how the snowball tossing learning model affects students' learning results in Khairun University's biology education study program. This study's methodology is quantitative, pre-experimental, and uses a single class as the experimental class. The t test and the one group pretest-posttest design are utilized for data analysis. According to the research findings, the mean value was -2.4250, the standard deviation was 11.50229, and the posttest average value following the implementation of the snowball tossing learning model was 74.75, which fell into the medium range. The t value is -9,428, the df value is 19, the mean error is 2,571, and the Sig. (2-tailed) is 0.000. Ha is approved because the t test results show that t count > t table. This indicates that the student learning outcomes scores on the pretest and posttest differ. These findings suggest that the snowball tossing learning strategy can enhance student learning outcomes in Khairun University's biology education study program..